فعالية اللعب الإبداعي القائم على تطبيقات الحوسبة التشاركية في تنمية مهارات البرمجة بالكائنات لدى تلاميذ الصف الثالث الإعدادي - يونس، أمين صلاح الدين أمين; عبدالله، أحلام محمد السيد (الجمعية المصرية للكمبيوتر التعليمي, 2017)
The current research aims to achieve the following objectives: 1 .Measuring the effectiveness of creative play in the development of cognitive aspects associated with the programming skills of objects among students of the preparatory journey. 2 .Measure the effectiveness of creative play in the development of performance aspects associated with the programming skills of objects among students of the preparatory journey. 3 .Measure the effectiveness of creative play in the development of performance aspects associated with the skills of programming with objects among students of the preparatory journey. Search tools: 1.Achievement test to measure the cognitive aspects associated with the programming skills of objects. 2.Note card to measure the performance aspects associated with programming skills with objects. 3 .Final Product Quality Assessment Card (program produced by students). Research sample: A random sample of (60) preparatory third grade students was selected. The results of the research revealed that creative play based on participatory computing applications is effective in developing the level of experimental group students of the research sample of programming skills with objects, because the use of educational games increased the motivation of learners. In light of the results, the researcher recommends the following: 1-employ creative play in the development of many of the skills needed by students in different stages of study. 2-Developing electronic courses based on games for kindergarten children. 3-The use of electronic games in teaching students with disabilities (audio, visual, mental, mental).
سعى البحث الحالي لتحقيق الأهداف الآتية: 1- قياس فعالية اللعب الإبداعي في تنمية الجوانب المعرفية المرتبطة بمهارات البرمجة بالكائنات لدى تلاميذ المرحلة الإعدادية. 2- قياس فعالية اللعب الإبداعي في تنمية الجوانب الأدائية المرتبطة بمهارات البرمجة بالكائنات لدى تلاميذ المرحلة الإعدادية. 3- قياس فعالية اللعب الإبداعي في تنمية الجوانب الأدائية المرتبطة بمهارات البرمجة بالكائنات لدى تلاميذ المرحلة الإعدادية. أدوات البحث: 1.اختبار تحصيلي لقياس الجوانب المعرفية المرتبطة بمهارات البرمجة بالكائنات. 2.بطاقة ملاحظة لقياس الجوانب الأدائية المرتبطة بمهارات البرمجة بالكائنات. 3.بطاقة تقييم جودة المنتج النهائي (البرنامج الذي ينتجه التلاميذ). عينة البحث: تم اختيار عينة عشوائية من تلاميذ الصف الثالث الإعدادي عددها (60). وقد أسفرت نتائج البحث عن أن للعب الإبداعي القائم على تطبيقات الحوسبة التشاركية فاعلية في تنمية مستوى تلاميذ المجموعة التجريبية من عينة البحث لمهارات البرمجة بالكائنات، وذلك يرجع إلى أن استخدام الألعاب التعليمية أدى إلى زيادة دافعية المتعلمين. وفي ضوء النتائج يوصي الباحث بما يلي: 1-توظيف اللعب الإبداعي في تنمية عديد من المهارات التي يحتاجها التلاميذ في المراحل الدراسية المختلفة. 2-تطوير مقررات إلكترونية قائمة على الألعاب لأطفال الروضة. 3-توظيف الألعاب الإلكترونية في التدريس للتلاميذ ذوي الإعاقات (السمعية، البصرية، العقلية، الذهنية). 4-الاهتمام بمحتوى ومهارات البرمجة وتطويرها وتدريسه بالأساليب الحديثة وليست التقليدية.
Keywords: تكنولوجيا التعليم -- مهارات البرمجة -- طلبة المرحلة الإعدادية